THE EFFECT OF CAR, NIM, BOPO, AND LDR ON ROA IN BUMN BANKS IN THE PERIOD 2013-2022 - Agnes Thandania Blessky; Herlin Munthe; Bayu Wulandari; Kiki Hardiansyah Siregar (ZILLZELL MEDIA PRIMA, 2023)
This study aims to see the effect of CAR (Capital Adequacy Ratio), NIM (Net Interest Margin), BOPO (Operating et al.), and LDR (Loan to Deposit Ratio) on ROA (Return on Assets) in BUMN Banks in the period 2013 - 2022. The data source for this research is secondary through the websites of each company listed on the Indonesia Stock Exchange. The population used in this study The population in this study are state-owned banks listed on the Bursa Efek Indonesia (BEI). The sample in this study is the financial statements of state-owned banks, namely Reports on Calculation of CAR, NIM, BOPO, LDR, and ROA financial ratios for 2013-2022, a total of 40 samples. The analysis technique used is R Square analysis and Path Analysis. The results of the study show that NIM and LDR have a positive effect on ROA. CAR and BOPO hurt ROA, while CAR, NIM, BOPO, and LDR affect ROA in R Square.